Priorities in the allocation of scarce resources - Boyd, K. M. (Journal of medical ethics, 1986)
The authors report and comment on student reactions to a clinical example of moral choice in the microallocation of scarce resources. Four patients require dialysis simultaneously, but only one kidney machine is available. What moral, as opposed to clinical, criteria are available to determine who should have priority?